Household Cookstoves, Environment, Health, and Climate Change : A New Look at an Old Problem - World Bank (Washington, DC, 2017)
Open fires and primitive stoves have been used for cooking since the beginning of human history. They have come in various sizes and styles, having been adapted to myriad cultures and food preparation methods. As society has progressed, more sophisticated stove models have been developed. Today's modern kitchens reflect the many types of standardized and specialized cooking devices available, from coffee and tea pots to toasters and gas cook tops. But in many developing countries worldwide, the poor still burn biomass energy to meet their household cooking needs. These open fires are fairly inefficient at converting energy into heat for cooking; the amount of biomass fuel needed each year for basic cooking can reach up to two tons per family. In addition, collecting this fuel sometimes can take an hour a day on average. Furthermore, these open fires and primitive cook stoves emit a significant amount of smoke, which fills the home; this indoor cooking smoke has been associated with a number of diseases, the most serious of which are chronic and acute respiratory illnesses, such as bronchitis and pneumonia. This report takes a fresh look at what new approaches might be used to tackle this well known yet complex multi-sector issue. Although there are other ways to reduce household air pollution, including inter fuel substitution and household ventilation, this study focuses mainly on the recently developed biomass cook stoves for developing countries and their financing models and sources. Known by many as 'advanced biomass cook stoves,' these new cook stoves generally have better energy-combustion properties and reduce fuel consumption by about half. Such innovations warrant the development of a more serious program to deal with both the emissions and health issues resulting from cooking with open fires or traditional biomass cook stoves.